Zika virus: advancing a priority research agenda for preparedness and response - Lackritz, Eve M; Ng, Lee-Ching; Marques, Ernesto T A; Rabe, Ingrid B; Bourne, Nigel; Staples, J Erin; Méndez-Rico, Jairo A; Harris, Eva; Brault, Aaron C; Ko, Albert I; Beasley, David W C; Leighton, Tabitha; et al. (The Lancet infectious diseases, 2025)
The 2015–16 Zika virus epidemic emerged in the Americas and rapidly spread throughout the region and beyond, showing the epidemic potential of this mosquito-borne Orthoflavivirus and its capacity to cause severe congenital malformations and neurological sequelae. WHO declared the Zika virus epidemic a public health emergency of international concern in 2016. Despite this declaration, there are no licensed Zika virus vaccines, therapeutics, or diagnostic tests appropriate for routine antenatal screening. To address this absence of essential tools to detect and mitigate the threat of future Zika virus outbreaks, a group of global experts developed a priority agenda for Zika virus research and development. This Series paper summarises crucial challenges and knowledge gaps and outlines a comprehensive strategy to advance research, surveillance, global capacity, policy, and investment for Zika virus preparedness and response.